A descriptive grammar of early Old Japanese prose - Bentley, John R. (Leiden ; Boston : Brill, 2001)
The oldest written stage of the Japanese language forms the subject of John Bentley's important volume. The underlying texts (also presented here) are those of the religious liturgies (norito) and imperial edicts (A.D. 685).
Table of Contents; List of Tables; List of Figures; List of Abbreviations; List of Symbols; Acknowledgements; Chapter 1: Introduction; Chapter 2: The Liturgies; Chapter 3: Phonology; Chapter 4: Nominals; Chapter 5: Verbs; Chapter 6: Verbal Suffixes; Chapter 7: Adverbs; Chapter 8: Particles; Chapter 9: Conjunctions; Chapter 10: Lexicon; Chapter 11: Conclusion; Appendix; Bibliography; Index.
Includes bibliographical references (pages 274-282) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Japanese language -- To 794 -- Grammar; Japanese language -- Grammar, Classical; Japonais (Langue) -- Jusqu'à 794 -- Grammaire; FOREIGN LANGUAGE STUDY -- Japanese; Japanese language -- Grammar; Japanese language -- Grammar, Classical; Religiöse Literatur; Deskriptive Grammatik; Japans; Língua japonesa; Gramática.; Altjapanisch; To 794; Electronic book